1997
DOI: 10.1111/j.1365-2699.1997.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of three ancient woodland soils in southern England

Abstract: Despite a wealth of published research on the nature of woodland soils, little is known about the nature of soils on sites that have supported woodland for many hundreds of years, namely ancient woodland. The properties and variability of soils in three ancient woods; one in the New Forest. Hampshire and two in Berkshire, were compared with those under recent woods. The acidity of ancient and recent woodland soils was high and remarkably similar. Only where cultivation of soils had preceded woodland establishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
8
38
1
1
Order By: Relevance
“…Wilson et al (1997), for example, found that soil pH of two matched pairs of ancient and recent woodlands to be similar, while total and organic P concentrations of the ancient woodland soils were greater than those under recent woodlands. Graae et al (2003), working on beech and oak stands in Southern Sweden, also failed to find differences in soil variables that could be directly attributed due to former land-use.…”
Section: Introductionmentioning
confidence: 95%
“…Wilson et al (1997), for example, found that soil pH of two matched pairs of ancient and recent woodlands to be similar, while total and organic P concentrations of the ancient woodland soils were greater than those under recent woodlands. Graae et al (2003), working on beech and oak stands in Southern Sweden, also failed to find differences in soil variables that could be directly attributed due to former land-use.…”
Section: Introductionmentioning
confidence: 95%
“…However, even after a long period of time, persistent differences between ancient and secondary woodland soils can be observed. Former arable land use generally results in increased nutrient levels, especially of P (Koerner et al, 1997;Wilson et al, 1997;Honnay et al, 1999). P is immobile and the total P content is stable (Binkley, 1986), although its availability decreases after the afforestation of farmland (Magid, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…It has also been shown that at least in some cases these effects persist long after the tree is gone, thus leaving a ''signature'' that provides information about tree spacing, forest characteristics, and other ecological variables (Mossa and Schumacher, 1993;Retallack, 1990;Schaetzl, 1990;Schaetzl and Follmer, 1990;Small et al, 1990;Stephens, 1956;Vasenev and Targul'yan, 1995;Wilson et al, 1997).…”
Section: Effects Of Individual Treesmentioning
confidence: 99%
“…Individual trees may have significant effects on soil morphology by several mechanisms, including a focus of organic-acid-enriched moisture flux, and by primary and secondary effects of tree throw (Boettcher and Kalisz, 1990;Crampton, 1982;Certini et al, 1998;Schaetzl, 1990;Schaetzl et al, 1989Vasenev and Targul'yan, 1995;Wilson et al, 1997;Zinke, 1962). It has also been shown that at least in some cases these effects persist long after the tree is gone, thus leaving a ''signature'' that provides information about tree spacing, forest characteristics, and other ecological variables (Mossa and Schumacher, 1993;Retallack, 1990;Schaetzl, 1990;Schaetzl and Follmer, 1990;Small et al, 1990;Stephens, 1956;Vasenev and Targul'yan, 1995;Wilson et al, 1997).…”
Section: Effects Of Individual Treesmentioning
confidence: 99%